2015
DOI: 10.5152/eurjrheumatol.2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous bursitis of the greater trochanter mimicking ankylosing spondylitis

Abstract: Tuberculous trochanteric bursitis (TTB) is a rare condition that accounts for 1% of musculoskeletal tuberculosis cases. Extrapulmonary TB is usually diagnosed late because of reduced diagnostic suspicion, particularly in the absence of signs of systemic infection. Herein, we report a case of right hip pain that was misdiagnosed as ankylosing spondylitis. The patient had a history of inflammatory back pain with morning stiffness. However, HLA-B27 was negative. Sacroiliac magnetic resonance imaging (MRI) reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Initially it was thought that TTB mainly affected young adults, however, more recent studies indicate that it can occur at any age, with a higher incidence in the elderly (average age 57 years). 3 No gender predilection has been documented. 2 The clinical presentation of TTB is often vague, characterized by chronic symptoms, such as pain and joint stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initially it was thought that TTB mainly affected young adults, however, more recent studies indicate that it can occur at any age, with a higher incidence in the elderly (average age 57 years). 3 No gender predilection has been documented. 2 The clinical presentation of TTB is often vague, characterized by chronic symptoms, such as pain and joint stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some studies advocate starting antibacillary medication before a definitive diagnosis is made in order to reduce the risk of mycobacteria spreading during surgery. 3,6 Several studies reported the reactivation of trochanteric tuberculosis after surgical drainage in the pre-chemotherapy era, also justified by the lack of knowledge about tuberculosis infection. 5 In this case, and as in many others, the difficulty in establishing this diagnosis was implicit, not only due to the vague, nonspecific and only local symptoms, but also because he was an immunocompetent patient, due to the initial AFB research, motivated by the histology of chronic necrotizing granulomatous bursitis (also present in brucellosis, coxiella, sarcoidosis), was negative and the patient suffered significant clinical improvement over 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations